The nucleoporin MEL-28 promotes RanGTP-dependent γ-tubulin recruitment and microtubule nucleation in mitotic spindle formation - Yokoyama, Hideki; Koch, Birgit; Walczak, Rudolf; Ciray-Duygu, Fulya; González Sánchez, Juan Carlos; Devos, Damien; Mattaj, Iain W.; Gruss, Oliver (Nature Communications, 2014)
The GTP-bound form of the Ran GTPase (RanGTP), produced around chromosomes, drives nuclear envelope and nuclear pore complex (NPC) re-assembly after mitosis. The nucleoporin MEL-28/ELYS binds chromatin in a RanGTP-regulated manner and acts to seed NPC assembly. Here we show that, upon mitotic NPC disassembly, MEL-28 dissociates from chromatin and re-localizes to spindle microtubules and kinetochores. MEL-28 directly binds microtubules in a RanGTP-regulated way via its C-terminal chromatin-binding domain. Using Xenopus egg extracts, we demonstrate that MEL-28 is essential for RanGTP-dependent microtubule nucleation and spindle assembly, independent of its function in NPC assembly. Specifically, MEL-28 interacts with the γ-tubulin ring complex and recruits it to microtubule nucleation sites. Our data identify MEL-28 as a RanGTP target that functions throughout the cell cycle. Its cell cycle-dependent binding to chromatin or microtubules discriminates MEL-28 functions in interphase and mitosis, and ensures that spindle assembly occurs only after NPC breakdown.